Exploring the association between housing insecurity and mental health among renters: A systematic review of quantitative primary and secondary studies - Mira Talmatzky; Laura Nohr; Christine Knaevelsrud; Helen Niemeyer (PLoS ONE, 2026)
Adverse social and economic conditions negatively impact mental health and well-being. To the best of the authors’ knowledge, the present systematic review is the first to investigate the association between housing insecurity and mental health outcomes among renters, with a focus on housing affordability and instability. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search was conducted in December 2022 across four databases (MEDLINE, PsycINFO, Web of Science, and ASSIA). Quantitative studies from OECD (Organisation for Economic Co-operation and Development) member countries were eligible for inclusion if they investigated housing insecurity by examining at least one independent variable related to housing affordability and/or instability, and included at least one mental health-related outcome among adult renters. Studies needed to specifically distinguish effects for renters, not simply adjust for tenure or include an interaction. Studies were excluded if they analyzed other forms of housing insecurity, examining residential satisfaction and general health outcomes, or populations other than adult renters (< 15 years of age). The methodological quality of the included studies was rated with the JBI Critical Appraisal Tools, and the certainty of evidence was rated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework. Due to heterogeneity of the identified studies, we performed a narrative synthesis. Twenty-two studies with sample sizes ranging from n = 89 to n = 179,037 met the inclusion criteria (resulting in a total sample size of at least N = 336,775), of which 14 applied a longitudinal design, five a cross-sectional design, and three a quasi-experimental design. Based on the JBI ratings, the overall methodological quality of the included studies was good. The overall ratings of certainty of evidence, based on the GRADE ratings, were between low and very low – mainly due to the non-controlled study designs of included studies. Among the nine studies examining housing affordability, six reported significant associations between unaffordable rent and poor mental health in low-income renters. Regarding housing instability, 12 out of 14 studies reported significant associations between unstable housing and renters’ mental health issues. Measures of housing insecurity varied, with rent-to-income ratio and forced moves being most commonly employed. Mental health outcomes focused primarily on overall mental health, well-being, and depressive symptoms, while few studies explored other mental health outcomes. Despite methodological limitations due to the non-controlled studies included in the review, the findings suggest overall that experiencing unaffordable or unstable housing has a negative impact on renters’ overall mental health and depressive symptoms. Housing insecurity poses a significant challenge for renters in OECD countries, highlighting the need for policymakers to implement supportive housing policies and tenure protection measures in order to improve renters’ housing security and ultimately public health. Nevertheless, more research with robust study designs is needed to draw further conclusions. The systematic review has been conducted without external funding. It has not been pre-registered and no study protocol has been published.